Mutational Analysis of the Rubella Virus Nonstructural Polyprotein and Its Cleavage Products in Virus Replication and RNA Synthesis - Liang, Yuying (American Society for Microbiology, 2000)
Rubella virus nonstructural proteins, translated from input genomic RNA as a p200 polyprotein and subsequently processed into p150 and p90 by an intrinsic papain-like thiol protease, are responsible for virus replication. To examine the effect of p200 processing on virus replication and to study the roles of nonstructural proteins in viral RNA synthesis, we introduced into a rubella virus infectious cDNA clone a panel of mutations that had variable defective effects on p200 processing. The virus yield and viral RNA synthesis of these mutants were examined. Mutations that completely abolished (C1152S and G1301S) or largely abolished (G1301A) cleavage of p200 resulted in noninfectious virus. Mutations that partially impaired cleavage of p200 (R1299A and G1300A) decreased virus replication. An RNase protection assay revealed that all of the mutants synthesized negative-strand RNA as efficiently as the wild type does but produced lower levels of positive-strand RNA. Our results demonstrated that processing of rubella virus nonstructural protein is crucial for virus replication and that uncleaved p200 could function in negative-strand RNA synthesis, whereas the cleavage products p150 and p90 are required for efficient positive-strand RNA synthesis.